SOUTHERN AFRICA: CHALLENGES AND OPPORTUNITIES FOR FSR/E - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The SADC countries have much to offer with their experiences in working with resource-poor farmers. Their professionals and technicians, like the black people of South Africa and Namibia, not only have an understanding of the resource-poor farming...